Nilai-nilai Kearifan Lokal Kampung Naga di Era Modernisasi - Derizal, Derizal; Nurbaeti, Nurbaeti; Gunawijaya, Jajang (LPPM Institut Pendidikan Nusantara Global, 2024)
Kampung Naga is a traditional village that upholds the customs, culture and beliefs of its ancestral heritage in the midst of modernization. This study aims to know and understand history, cultural elements of the livelihood system, social and community systems, religious values, arts and technology, as well as identify the values of local wisdom from the people of Kampung Naga. The data collection technique used is a type of qualitative research prioritizing observation techniques, in-depth interviews and documentation to Kuncen, Guide,and a Society of Kampung Naga. The results show that Kampung Naga is able to maintain customs even though it is in the modernization era. The five elements of culture are livelihoods, social and organizational systems, arts and technology.